ANALISA PENGARUH PENGOPERASIAN FILTER AKTIF TERHADAP RUGI-RUGI DAYA DAN DERATING TRAFO PADA SISTEM KELISTRIKAN DI RS BIMC NUSA DUA - Marta Pratama, A.A. Gede; Rinas, I Wayan; Maharta Pemayun, Anak Agung (Jurnal SPEKTRUM; Vol 8 No 3 (2021): Jurnal SPEKTRUM, 2021)
Nonlinear loads are harmonic current sources for utilities. High harmonic levels greatly increase the loss of electrical energy. The quality of electric power is determined by the parameters of power losses that appear in the electrical system of BIMC Nusa Dua Hospital due to harmonic distortion. In this study, THD analysis was carried out based on the results of measurements and simulations according to the IEEE 519-2014 standard, analysis of power loss due to THD current due to non-linear loads, and analysis of power loss after installation was carried out. Active filter, calculation of the working capacity of the transformer before and after installing an active filter.